Burden of disease, treatment utilization, and the impact on education and employment in patients with sickle cell disease: A comparative analysis of high‐ and low‐ to middle‐income countries for the international Sickle Cell World Assessment Survey. Issue 8 (20th June 2022) - Osunkwo, Ifeyinwa; James, John; El‐Rassi, Fuad; Nero, Alecia; Minniti, Caterina P.; Trimnell, Cassandra; Paulose, Jincy; Ramscar, Nicholas; Bailey, Tom; Rajkovic‐Hooley, Olivera; Andemariam, Biree
Abstract: The international Sickle Cell World Assessment Survey (SWAY) reported a high impact of sickle cell disease (SCD) on patients' daily lives globally. In this study, we analyzed whether the reported burden differed between patients from the USA ( n  = 384) and other high‐income (HI; n  = 820) or low‐ to middle‐income (LMI; n  = 941) countries. We assessed symptoms and complications, incidence/management of vaso‐occlusive crises (VOCs), treatment utilization/satisfaction, and the impact of SCD on education/employment. Certain symptoms (bone aches, insomnia, and joint stiffness) and complications (swollen/painful fingers/toes, gallstones, vision problems, blood clots, and asthma) were reported proportionally more by patients in the USA than in the HI/LMI countries. Self‐reported VOCs were more common (mean [SD]: 7.1 [5.7] vs. 5.5 [8.9] and 4.4 [4.6] in the previous 12 months) and were managed more often by hospitalization (52% vs. 24% and 32%) in the USA than the HI and LMI countries. A higher proportion of patients from the USA than the HI/LMI countries reported a negative impact of SCD on their employment/schooling. Although high overall satisfaction with current treatments was reported globally, most patients indicated a strong desire for alternative pain medications. There are likely several reasons for the relatively high patient‐reported burden in the USA group compared with the HI/LMI countries, including an older population and differences in newborn screening programs and pediatric/adult transition of care. It is clear that there is an urgent need for improved understanding and management of SCD globally, not just in the USA.